Doctors' perceptions of pressure from patients for referral. Issue 6786 (18th May 1991) - Armstrong, D; Fry, J; Armstrong, P
Abstract : OBJECTIVE–To assess the effect of pressure from patients on patterns of general practitioners' outpatient referrals. DESIGN–Survey of general practitioners' referrals to hospital outpatient departments during one week. SETTING–One health district. SUBJECTS–All (160) general practitioners in the health district. MAIN OUTCOME MEASURES–Specialty of the referral, the reason for it, and its status (NHS or private) and the general practitioner's assessment of the degree of pressure exerted by the patient for the referral (much, little, or none). RESULTS–122 (76%) general practitioners completed the survey. Younger general practitioners (aged less than or equal to 45) and those qualifying in the United Kingdom and Republic of Ireland reported greater pressure from patients to refer (p less than 0.03, p less than 0.001 respectively). Pressure was also greater for patients referred privately (p less than 0.001), for those referred for reassurance (p less than 0.05), and for those referred to clinics in psychiatry, rheumatology, dermatology, and orthopaedics. General practitioners with a higher referral rate (with total consultations in the week as the denominator) were more likely to report pressure (p less than 0.01). CONCLUSIONS–The pressure from patients to refer reported by general practitioners is related both to general practitioners' characteristics and to the nature of the referral. Pressure to refer seems to explain some of the variation in referral rates among general practitioners.